"Control interno a las políticas de crédito y cobranza y su efecto en la rentabilidad de la empresa comercial Dávila, cantón La Mana, año 2013" - Rivera Chugchilán, Diana Aracely (2016)
This thesis research was developed at the Davila-owned Business Enterprise Ing. Luis Ledesma Davila, which has been operating since 2008, offering citizenship lamanense a wide range of appliances, motorcycles and computers. Considering the importance of internal control in business management and knowledge of people to achieve optimization on the results of operations management is necessary to define the role played by companies. With the main objective evaluation of internal control over the credit and collection policies and their effect on the profitability of the business enterprise Davila Cantón La Mana, 2013; using methods and research techniques such as customer surveys and interview the owner, whose analysis by COSO components I; It identified a number of findings that affect the normal development of its activities; among the main one can cite the lack of manual functions, the lack of policies; moreover, the absence of monitoring the granted credits are highlighted, since they do not possess a flow chart, just as you can establish that the absence of a structural organization causes confusion in the daily work of the business enterprise to be a worrying weakness .For this reason a report outlining the findings with their findings and recommendations which are analyzed suggested and implemented by the manager with the support of colleagues in this way helping to improve profitability and customer satisfaction was developed.